2016
DOI: 10.1007/s10578-016-0639-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Attachment Representations in Adolescents: Discriminant Validation of the Adult Attachment Projective Picture System

Abstract: The contribution of attachment to human development and clinical risk is well established for children and adults, yet there is relatively limited knowledge about attachment in adolescence due to the poor availability of construct valid measures. The Adult Attachment Projective Picture System (AAP) is a reliable and valid instrument to assess adult attachment status. This study examines for the first time the discriminant validity of the AAP in adolescents. In our sample of 79 teenagers between 15 and 18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 50 publications
3
27
1
1
Order By: Relevance
“…We assessed attachment representations and the amount of unresolved attachment characteristics using the Adult Attachment Projective Picture System (AAP). This is a valid and reliable interview procedure for classifying adolescent (Gander, George, Pokorny, & Buchheim, 2016) and adult attachment representations ( George & West, 2012). By using a set of standardized questions, individuals are asked to tell a story in response to one neutral (warm-up) and seven attachment-related picture stimuli depicting scenes of solitude, death, separation, and fear.…”
Section: Methodsmentioning
confidence: 99%
“…We assessed attachment representations and the amount of unresolved attachment characteristics using the Adult Attachment Projective Picture System (AAP). This is a valid and reliable interview procedure for classifying adolescent (Gander, George, Pokorny, & Buchheim, 2016) and adult attachment representations ( George & West, 2012). By using a set of standardized questions, individuals are asked to tell a story in response to one neutral (warm-up) and seven attachment-related picture stimuli depicting scenes of solitude, death, separation, and fear.…”
Section: Methodsmentioning
confidence: 99%
“…Coders can classify the protocols into four attachment groups: secure (F), insecure‐dismissing (Ds), insecure‐preoccupied (E), and unresolved (U). Psychometric properties were tested in several studies for adolescents and adults (Buchheim et al, ; Gander, George, Pokorny, & Buchheim, ; George & West, ), and the AAP demonstrates a high convergent agreement with the Adult Attachment Interview but requires half of the time to administer and rate the interviews (George & West, ). A recent study on adult patients with chronic depression compared with healthy controls demonstrated a high convergent validity between the AAP and the AAI ( n = 30, κ = 0.885, ASE = 0.112), p < 0.001, simple agreement 94% (Buchheim et al, ).…”
Section: Methods and Designmentioning
confidence: 99%
“…Second, the control sample was made up largely of middle-class subjects with a limited ethnic diversity. Whereas sociodemographic variables like educational levels, gender, or age do not seem to be associated with attachment classifications in adolescents (Gander et al, 2016), our results may not be generalizable to populations with different ethnic backgrounds. Furthermore, most of the parents from the clinical group were divorced, whereas the majority of parents from the control group were married.…”
Section: Attachment and Childhood Traumamentioning
confidence: 99%
“…There are two kinds of adolescent assessments that predominate the field including self-report and interview. The most popular kind of assessment and the only one to be discussed however is the Adult Attachment Interview (AAI) (Gander et al, 2017). The AAI was developed by Main and Goldwyn from 1985to 1996 and…”
Section: Attachment and Adolescentsmentioning
confidence: 99%
“…It was designed to "surprise the unconscious" (Warmuth & Cummings, 2015, p. 202) and assess the relationships with parents during childhood from a current state of mind . It was initially developed for adults and later extended to include adolescents (Warmuth & Cummings, 2015), and it is considered the "gold standard" for assessing attachment in adolescence (Gander et al, 2017).…”
Section: Attachment and Adolescentsmentioning
confidence: 99%